The impact of work related and personal related stressors on job performance among public school teachers in Kota Kinabalu Sabah - Olisa Albert (2014)
The objective of this study was to identify the significant predictors of stress amongst teachers and examine its influence on job performance among school teachers. Work related stressors (consisting of work overload; student discipline and motivation) and personal related stressors (consisting of family matters, financial distress) were selected as independent variables and job performance as a dependent variable. Gender as a moderator was also selected. A total of 160 questionnaires were distributed at selected schools in Sabah, namely Sk Kibabaig Penampang, Sk Sri Gaya Kata Kinabalu, SMK Perempuan Likas, Sk St Paul Penampang, Sk Telupid Telupid, Sk Ratau Ranau, Sk Gabungan Telupid, Sk Surati Papar, Sk Pekan Papar, and Sk St Mary Papar. Total of 134 copies were returned and only 110 copies were usable. Data analysis was conducted using SPSS and PLS. Work related variables were found to be significant stressors to job performance, while personal related stressors were not significant. Gender had no moderating effect on the relationship between stressors and job performance amongst these school teachers. Managerial and practical implications highlight the importance of addressing work overload for teachers, as well as the issue of student discipline and motivation, as both these factors affect job performance amongst teachers in the selected schools in this study.